Pancreatic adenocarcinoma presenting as acute large bowel obstruction: case report - Gil, Inês Campos (2018)
Introduction: Acute large bowel obstruction is a rare presentation of pancreatic cancer, with only six cases described in the revised literature. In all those cases, diagnosis was made either intraoperatively or post-mortem. Case presentation: A 63-year-old man presented in the emergency room with 4 days of bowel constipation associated with abominal pain and distention. Abdominal CT revealed a narrowing at the colonic splenic flexure and the colonoscopy revealed extrinsic compression at 40 cm from the anal verge. The patient was submitted to emergent exploratory laparotomy. We identified a mass involving the colonic splenic flexure, splenic hilum and the pancreatic tail. An en bloc subtotal colectomy, splenectomy and distal pancreatectomy was performed. Final pathology revealed a pancreatic ductal adenocarcinoma. The postoperative period was complicated with fecal peritonitis due to bowel perforation (day 3), hemoperitoneum secondary to pancreatic stump bleeding (day 10) and surgical site infection. The patient was discharged home on day 43. Conclusion: A high level of suspicion is necessary to take into account pancreatic carcinoma as a differential diagnosis of bowel acute obstruction.